Underexpression of PPAR gamma is associated with aneuploidy and lower differentiation of thyroid tumours of follicular origin - Espadinha, C. (2022)
Funding: This study was supported by Fundação para a Ciência e Tecnologia (POCTI/CBO/48922/2002), Portugal.